2022
DOI: 10.1097/prs.0000000000009408
|View full text |Cite
|
Sign up to set email alerts
|

Suspensionplasty for Revision Thumb Carpometacarpal Osteoarthritis Surgery: Comparing Suture Button Suspensionplasty to Ligament Reconstruction and Tendon Interposition

Abstract: uture button suspensionplasty has gained favor over the past decade as an alternate to ligament reconstruction and tendon interposition for treatment of thumb carpometacarpal osteoarthritis. Its advantages include its inherent initial stability, allowing for early mobilization, 1,2 and its capacity to resist first metacarpal subsidence more effectively than ligament reconstruction and tendon interposition. 3,4 Although favorable outcomes have been reported in primary cases, 5 suture button suspensionplasty has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, these surgeries require rigid immobilization for four to six weeks before the range of motion exercises can be initiated. Guerrero et al compared LRTI to SBS and concluded SBS is an effective option for the surgical revision of CMC arthritis [19]. SBS has a shorter intraoperative, return-towork, and immobilization time when compared to LRTI [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, these surgeries require rigid immobilization for four to six weeks before the range of motion exercises can be initiated. Guerrero et al compared LRTI to SBS and concluded SBS is an effective option for the surgical revision of CMC arthritis [19]. SBS has a shorter intraoperative, return-towork, and immobilization time when compared to LRTI [11].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the optimal treatment of symptomatic instability of the thumb metacarpal bone (Hansen, 2022). Most commonly, a combination of partial resection of the base of the thumb metacarpal bone and renewal of the suspension and/or interposition is performed (Braun et al., 2012; Cooney et al., 2006; Guerrero et al., 2022; Herren et al., 2021; Hess et al., 2018; Johnson and Chung, 2022; Ledoux, 2021). Different techniques and interposition materials have been reported, the most noted being an untouched FCR or part of the APL tendon (Dawood et al., 2022; Hamasaki et al., 2021; Marks et al., 2017; Vermeulen et al., 2011).…”
Section: Complications Based On the Different Treatment Interventionsmentioning
confidence: 99%
“…Several biomechanical studies have indicated that suture suspension might add to the stability of the thumb metacarpal after trapeziectomy, but most of these were either in vitro biomechanical studies (Dréant, 2021; Friebel et al., 2018; Hooke et al., 2016; Morais et al., 2022) or with low patient numbers or short follow-up periods (Assiotis et al., 2017; DeGeorge et al., 2019). Some studies do confirm that suspensionplasty helps to maintain a wider trapezial space compared to RSI alone, but without any differences in clinical outcomes (Ferrão et al., 2023; Guerrero et al., 2022; Hooke et al., 2016; Morais et al., 2022). A more uncommon revision option is fusion of the thumb metacarpal to the index metacarpal.…”
Section: Complications Based On the Different Treatment Interventionsmentioning
confidence: 99%